Loan purpose and accounting based debt covenants. Issue 2 (13th May 2019) - Paik, Daniel Gyung; Hamilton, Timothy; Lee, Brandon Byunghwan; Yoon, Sung Wook
Abstract : Purpose: The purpose of this paper is to investigate the association between the purpose of a loan and the type of debt covenants, separated into balance sheet-based and income statement-based covenants. Design/methodology/approach: Using private loan deal observations obtained from the DealScan database over the period between 1996 and 2013, the authors classify the sample loan deals into three categories based on the purpose of borrowing, namely, borrowings for corporate daily operating purposes, financing purposes and acquisition and investing purposes. The authors conduct multinomial logistic regression analysis to test the relationship between the choice of financial ratios in a debt covenant and the purpose of a loan, controlling for financing constraints and other factors that have been identified as important to debt covenant analysis in prior studies. Findings: The results provide evidence that the purpose of the loan is significantly associated with the type of debt covenants, suggesting that the lender and the borrower have considered the loan purpose when structuring their debt agreements. More specifically, the results indicate that the loans borrowed to fund acquisitions or long-term investment projects are more likely to have income statement-based covenants and less likely to have balance sheet-based covenants. In contrast, the loans borrowed for corporate daily operating purposes or financing purposes are more likely to contain balance sheet-based covenants relative to income statement-based covenants. Research limitations/implications: The authors show that loan purpose is significantly associated with the choice between income statement-based and balance sheet-based covenants. This result further illustrates ways in which accounting information improves contracting efficiency. The results are limited to the US market with its institutional structure. In future studies, it would be interesting to perform similar investigations on firms in other countries. Practical implications: The findings contain important and economically significant implications indicating that loan lenders and borrowers agree to include different types of accounting information (that is, income statement- versus balance sheet-based financial ratios) in their loan covenants for different purpose loans. Social implications: Overall, the results provide important evidence regarding the connection between debt covenant structure and loan purpose. In doing so, it contributes to the literature on debt contract design (Dichev and Skinner 2002; Chava and Roberts 2008; Demerjian 2011; Christensen and Nikolaev 2012). Despite much interest in debt contract design, Skinner (2011) argues that there still exists incomplete knowledge of the economic factors that structure debt contracts. Income statement-based covenants depend on measures of profitability and efficiency and act as trip wires that transfer control rights to lenders when borrowing firms' performance deteriorates. On the other hand, balance sheet-based covenants rely on information about sources and uses of capital and align interests between borrowing firms and lenders by restricting the borrower's capital structure. The authors show that loan purpose is significantly associated with the choice between income statement-based and balance sheet-based covenants. This result further illustrates ways in which accounting information improves contracting efficiency. Originality/value: This study is the first to identify differences in trends over time for the use of income statement- and balance sheet-based covenants as it relates to different loan purposes. The authors build on prior research to examine the degree to which loan purpose is associated with the choice between income statement-based and balance sheet-based covenants.